Eight Graduate Profiles: Strategies for Developing Student Character in the Digital Era - Rohmah, Rissana Aprilia; Yuanita, Pita; Winarni, Dian (Universitas Pahlawan Tuanku Tambusai, 2025)
In today's digital era, educational transformation requires strengthening the character that is integrated in technology-based learning. In modern character learning strategies, the eight dimensions of graduate profiles (DPL) are the basis for character education. The 8 DPL include faith and piety to God Almighty, citizenship, critical reasoning, creativity, collaboration, independence, health, and communication. In digital era learning, the integration of 8 DPLs can be achieved through the use of information and communication technology, hybrid learning, project-based learning, collaborative learning, and digital literacy. These methods can be used to shape and train students' character in a contextual, reflective, and sustainable manner. In online activities, students engage in online discussions, create digital works, create innovative presentations, think through blogs, and create digital character portfolios. By utilizing digital media, teachers act as facilitators, role models, and mentors. Teachers help students learn to collaborate across subjects, think critically, and communicate well through digital platforms. In addition, digital citizenship and digital health are also very important to maintain the safety, ethics, and well-being of students in the virtual environment. Schools, families, and digital communities work together to maintain character formation both in the real and virtual worlds. By implementing an 8-DPL-based learning strategy that is adaptive to technology, graduates are expected to become unique individuals, proficient in technology, and ready to compete and contribute in the era of globalization and digitalization.